Hörgeräteversorgung für Erwachsene - Berger, Thomas; Meuret, Sylvia; Dietz, Andreas (Laryngo-Rhino-Otologie, 2017)
Zu den grundlegenden Aufgaben des Hals-Nasen-Ohren-Arztes zählen die Diagnostik und Behandlung von Hörstörungen. Hierbei kommt der Hörgeräteversorgung eine besondere Rolle zu. Neben dem Wissen um die allgemeine Funktionsweise der unterschiedlichen Hörgerätetypen ist es hilfreich, weitere Hilfsmittel sowie die audiologischen und anatomischen Grenzen der konventionellen Hörgeräteversorgung zu kennen.The identification and treatment of hearing disorders belong to the fundamental tasks of an ENT-specialist. In this context the fitting of hearing aids has a special relevance. To verify a highly qualified medical care the knowledge of the audiological threshold values for the indication of the fitting of hearing aids and the detection of early signs for impaired communication are essential. The current quality assurance agreement defines technical and steric conditions pertaining to hearing aid fitting in the context of statutory health insurance. Only after approval of these postulated requirements the attending physician is allowed to bring to account his effort. The current regulations on medical devices specify both the basic requirement for a medical prescription and the expenses for hearing aids that are covered by the healthy insurances. A qualified hearing aid fitting is only possible if the ENT-specialist not only prescribes the device, but also conscientiously checks the comparative adjustments made by the hearing aid acoustician. Beside the knowledge about the general mode of operation and the different types of hearing aids ENT-specialist should know audiological and anatomic limits for the fitting of hearing aids.
Keywords: Hörgerät; Hörgeräteversorgung; Qualitätssicherungsvereinbarung; Hilfsmittel-Richtlinien; HdO-Geräte; Lautheitsskalierung